Slikanje s superparamagnetnimi nanodelcI - Stokelj, Eva (Matrika, 2018)
The subject of the article is new method of tomographic imaging using the nonlinear response of magnetic nanoparticles. The article describes the operation of this techique and its advantages over already used techniques in medicine.
Keywords: magnetism; magnetizem; medical imaging; medicinsko slikanje; superparamagnetic nanoparticles; superparamagnetni nanodelci